Estudo do desenvolvimento muscular e enzimático inicial do jundiá (Rhamdia quelen) com alimentos de origem animal e vegetal - Rossato, Suzete (2015)
The aim of this study was to evaluate the viability of using diets composed of ingredients of plant and animal origin in the feeding of post-larvae jundiá (Rhamdia quelen) and its influence on the development of animals. Experiments were carried out where it is tested in the first (E1) the total replacement (30%) and partial (15%) of the liver poultry for fish meal (FJ) and / or protein soy concentrate (CPS) on the standard diet containing 30% liver poultry. In the second (E2) substitution levels (5; 10; 15; 20 and 25%) of the liver by FJ and third (E3) of the liver levels for CPS replacement (15, 20, 25 and 30%) supplemented with taurine (CPST). Performance parameters were analyzed (weight, total length, condition factor, specific growth rate, daily weight gain, survival and product weight versus survival), muscle development (fiber diameter, number of fibers / mm² and total number of fibers ) and enzymatic activity (trypsin, chymotrypsin, lipase, amylase and maltase). The best performance of jundiá post-larvae was from 15FJ diets (E1 and E2) and 15CPST (E3). In the muscle development is found larger diameter and total number of fibers with the above mentioned diets. The development of the digestive system was not affected by the diets provided to post-larvae in this study. The enzymes assessed were already present and active at the first feeding. The enzyme activity varied during all experimental periods, with reduced activity of trypsin and chymotrypsin for diets with higher percentages of CPST over those with a lower percentage. According to the results we conclude that the combination of the sources of animal and plant improved the diet, helping improve the development of post-larvae of jundiá.